Pelatihan Pembuatan Keripik Pare Dalam Meningkatkan Nilai Tambah Ekonomi Buah Pare Pada Ibu-Ibu KWT di Desa Bendewuta Kecamatan Wonggeduku - Endang Sumiratin; Kadek Ariati (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2023)
The aim of holding this PKM activity is to diversify bitter melon fruit into chips for the women of KWT Medulu, Bendewuta Village, Wongeduku District. The selected participants were 10 people who had bitter melon gardens in their yard. The activity stages were lecture and practice. PKM activities were carried out well, participants were very enthusiastic in taking part in PKM activities. Monitoring results showed that the amount of increase in participants' knowledge and skills increased from 100%, from 10 participants who answered that they did not know before the training activity in making bitter melon chips, it increased to 100% or 10 participants answered that they knew and were able after the training. This shows that training activities can be said to be successful because there is an increase in the knowledge and skills of the training participants.